Primary care contact, clinical management, and suicide risk following discharge from inpatient mental health care: a case–control study - Rebecca Musgrove; Matthew J Carr; Nav Kapur; Carolyn A Chew-Graham; Faraz Mughal; Darren M Ashcroft; Roger T Webb (BJGP Open)
Background: Evidence is sparse regarding service usage and the clinical management of people recently discharged from inpatient psychiatric care who die by suicide. Aim: To improve understanding of how people discharged from inpatient mental health care are supported by primary care during this high-risk transition. Design & setting: A nested case–control study, utilising interlinked primary and secondary care records in England for people who died within a year of discharge between 2001 and 2019, matched on age, sex, practice-level deprivation, and region with up to 20 living discharged people. Method: We described patterns of consultation, prescription of psychotropic medication, and continuity of care for people who died by suicide and those who survived. Mutually adjusted relative risk estimates were generated for a range of primary care and clinical variables. Results: More than 40% of patients who died within 2 weeks of discharge and >80% of patients who died within 1 year of discharge had at least one primary care consultation within the respective time periods. Evidence of discharge communication from hospital was infrequent. Within-practice continuity of care was relatively high. Those who died by suicide were less likely to consult within 2 weeks of discharge (adjusted odds ratio [AOR] 0.61 [95% confidence interval CI = 0.42 to 0.89]), more likely to consult in the week before death (AOR 1.71 [95% CI = 1.36 to 2.15]), be prescribed multiple types of psychotropic medication (AOR 1.73 [95% CI = 1.28 to 2.33]), experience readmission, and have a diagnosis outside of the ‘severe mental illness’ definition. Conclusion: Primary care clinicians have opportunities to intervene and should prioritise patients experiencing transition from inpatient care. Clear communication and liaison between services is essential to provide timely support.